An exploratory study into the determinants of adoption of mobile TV services: an integrated value perspective - Borges, M. S. (2016)
While promising appealing benefits to consumers and increased revenues for stakeholders, mobile TV success remains very uncertain with disappointing adoption levels. The literature suggests that there is no comprehensive theoretical framework for explaining the adoption of mobile TV services. Our paper aims to propose a new theoretical framework for better understanding of consumers' adoption of new mobile TV services. The paper outlines major issues drawn from the extensive literature review and an exploratory qualitative study that we carried out. We present a new comprehensive value-centric framework that integrates theories and constructs from different fields of research. As such, it fulfils identified theoretical gaps while providing orientation to managers who deal with the development and implementation of new mobile services.